2017
DOI: 10.4103/ijt.ijt_43_16
|View full text |Cite
|
Sign up to set email alerts
|

Presence of mast cells and mast cell degranulation in scalp biopsies of telogen effluvium

Abstract: Background:Telogen effluvium (TE) is a type of acquired, diffuse alopecia that occurs due to an abnormal shift of scalp hair follicles from anagen to telogen, leading to premature shedding of hair. Previous studies have suggested the existence of a neuroimmunologic “brain-hair follicle” axis, in which mast cells have been implicated as an important link between the nervous system and immunologic system.Objective:The current study sought to investigate the role of mast cell presence and mast cell degranulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…In agreement with our study, previous studies showed statistical increase in the serum TGF-β 1 level in AA patients in comparison to controls [32][33][34]. On the other hand, in a study by Tembhre and Sharma, when AA patients were compared to controls, their serum TGF-β 1 levels were considerably lower.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our study, previous studies showed statistical increase in the serum TGF-β 1 level in AA patients in comparison to controls [32][33][34]. On the other hand, in a study by Tembhre and Sharma, when AA patients were compared to controls, their serum TGF-β 1 levels were considerably lower.…”
Section: Discussionsupporting
confidence: 92%
“…Grace et al . [ 10 ] also evaluated the follicular and non-follicular mast cell counts in patients with AA and AGA and reported similar mast cell counts with our results. Correspondingly, in their study, AA and AGA patients had significantly higher follicular and non-follicular mast cell counts than the healthy group.…”
Section: Discussionsupporting
confidence: 80%
“…Mast cells in mammalian skin are located in the dermis and subcutaneous tissue, especially in the connective tissue sheath of hair follicles and are involved in the hair folliclecycle [ 12 - 14 ]. A few studies have reported an increase in the number of mast cells in the perifollicular and perivascular in AA lesions [ 10 , 15 , 16 ]. Due to the importance of mast cells in non-scarring alopecias, the current study investigated the number of perifollicular and perivascular mast cells in AA and AGA lesions and compared them with healthy condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47] Telogen effluvium TE is a common non-scarring alopecia that mainly affects women. [47][48][49][50] It consists of diffuse hair loss occurring 2-3 months after a triggering event and lasting about 6 months; this hair loss leads to an abnormal shift of scalp hair follicles from anagen to telogen, resulting in premature hair shedding. [47][48][49] TE can be caused by low ferritin, vitamin B12 deficiency, thyroid dysfunctions, systemic diseases, drugs, medications, fever, stress, weight loss and giving birth.…”
Section: Non-scarring Alopeciamentioning
confidence: 99%